2008
DOI: 10.1007/s10562-008-9457-x
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biodiesel via Deoxygenation of Stearic Acid over Supported Pd/C Catalyst

Abstract: High catalytic activity was achieved in the deoxygenation of stearic acid in dodecane in a temperature range of 270-300°C under 17 bar helium over palladium on nanocomposite carbon Sibunit. Besides n-heptadecane, which was obtained previously in this reaction with palladium on activated carbon, n-pentadecane was also formed in significant amounts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(69 citation statements)
references
References 16 publications
(28 reference statements)
3
64
1
1
Order By: Relevance
“…71,[74][75][76][77][78][79][80][81][82][83][84] As evidenced by some reports, improvement in Pd-based catalysts in continuous operation may be necessary because some reports suggest they are hindered by rapid deactivation. Maki-Arvela et al 74 reported that the deactivation of a Pd catalyst while decarboxylating lauric acid may have been due to poisoning by the product gases (CO and CO 2 ) and/or coking.…”
Section: Biodieselmentioning
confidence: 99%
“…71,[74][75][76][77][78][79][80][81][82][83][84] As evidenced by some reports, improvement in Pd-based catalysts in continuous operation may be necessary because some reports suggest they are hindered by rapid deactivation. Maki-Arvela et al 74 reported that the deactivation of a Pd catalyst while decarboxylating lauric acid may have been due to poisoning by the product gases (CO and CO 2 ) and/or coking.…”
Section: Biodieselmentioning
confidence: 99%
“…[108] Studies of deoxygenation reactions were performed using palladium supported on the synthetic mesoporous carbon Sibunit. [114][115][116] Sibunit is a class of porous carbon-carbon composite materials combining advantages of graphite (chemical stability and electric conductivity) and activated carbon (high specific surface area and adsorption capacity). [117][118][119] Catalytic deoxygenation of technical-grade stearic acid containing a mixture of 59 % palmitic acid and 40 % strearic acid was demonstrated over 4 wt % Pd/C(Sibunit) at 300 8C under 17 bar of 5 vol % H 2 in argon.…”
mentioning
confidence: 99%
“…Synthesis of esters or biodiesel was reported by Lestari et al (2008). They synthesized biodiesel/esters via deoxygenation of carboxylic acids over supported Pd/C catalyst.…”
Section: Resultsmentioning
confidence: 99%